Penggunaan analisis diskriminan terhadap faktor-faktor yang mempengaruhi prestasi belajar transformasi geometri siswa SMP - Nurul Anisa Rahmawati; Ch Krisnandari Ekowati; Fransiska Atrik Halim (Mandalika Mathematics and Educations Journal, 2025)
Learning achievement is the result of a learning activity accompanied by changes achieved by a person (student) expressed in the form of symbols, numbers, letters, or sentences as a measure of the student's success levels. This study aims to determine the discriminant model and factors that significantly affect the learning achievement of geometry transformation in class IX UPTD SMP Negeri 4 Kupang. The subjects in this study were students of class IX UPTD SMP Negeri 4 Kupang which amounted to 100. The type of research in this study is quantitative research while the method used is survey method. Data analysis techniques in this study used discriminant analysis for two groups analyzed using SPSS software. From the results of the study obtained a discriminant model of the factors that affect the learning achievement of geometry transformation of class IX students in UPTD SMP Negeri 4 Kupang, namely  where D is student learning achievement and X1 is learning motivation. The factor that has the most significant effect on the learning achievement of geometry transformation of grade IX students in UPTD SMP Negeri 4 Kupang is learning motivation.